Let's get together and feel all right - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
A computer-mediated information system was launched in May 2000 for the benefit of some 50,000 small farmers in Jamaica. It will provide them with better access to useful, timely and accurate agricultural market information. The emphasis is on...